Desempenho produtivo e perfil metabólico de vacas primíparas F1 holandes x gir e sua relação com a reprodução - Adolfo Pérez Fonseca (2021)
This work was carried out with the following objectives: a) to describe the metabolic profile of primiparous F1 Holstein x Gyr cows raised in a free stall barn system during the period of transition. The bodily condition score was monitored before and after birth. Blood was collected weekly on the -21th, -14th and -7th day before birth, on the birth day (D0) and on the 7th, 14th and 21st days for glucose and urea analysis, and on the -7th day before birth and 7th, 14th and 21st days after birth for non-esterified fatty acid and beta-hydroxybutyrate analysis. The bodily condition score was greater on the last week before birth (3.9 ± 0.19) and differed to the 7th, 14th and 21st days after birth that showed a score of 3.70 ± 0.20; 3.67 ± 0.27 and 3.8 ± 0.22 respectively. Furthermore, the bodily condition score did not differ among the days after birth, on the first 21 days of lactation. The glucose concentrations were similar in both before and after birth days. The urea concentrations maintained unaltered from before birth to after birth except for the 7th day after birth where a decrease in the concentrations was evidenced. For the beta-hydroxybutyrate the concentrations increased gradually from before birth until the 21st day after birth. The concentrations of the non-esterified fatty acids decreased from before birth until the 21st day after birth; b) to describe the blood metabolic profile, the follicular fluid and its correlation with the quantity of aspired oocytes in different periods after birth in primiparous F1 Holstein x Gyr cows in lactation. Oocyte collections were made using a technique of follicular aspiration guided by transvaginal ultrasound on the days 30 ± 2, 60 ± 2 and 100 ± 2 after birth. On the same days of the oocyte collections, blood was also collected through coccygeal intravenous puncture and follicular fluid from the dominant follicle, which were used for glucose analysis, non-esterified fatty acids (NEFA), beta-hydroxybutyrate (BHBA), and urea. Recently after the recovery of the oocytes they were sent to the laboratory where the recovery rate, in vitro maturation and apoptosis through the TUNEL technique. The average concentration of glucose on the 30th day was higher on the follicular fluid than in the plasma, however on the 60th and 100th day after birth there was no difference among the glucose concentrations. The urea concentrations on the 30th, 60th and 100th days did not display difference on the plasma as much as on the follicular fluid, nonetheless, it was observed that the average concentrations of urea on the follicular fluid were significatively inferior to the plasma. The BHBA did not disclose noticeable differences between the concentrations of the follicular fluid and the blood serum among the 30th, 60th and 100th days after birth. The concentrations of the NEFA did not evidence differences between the concentrations in the blood serum and the follicular fluid on the 30th, 60th and 100th days after birth. There was no difference in the total production of oocyte in-between the collection times, however it was observed that the collections done between the 30th and 60th days evidenced less viable oocyte percentiles than those collected on the 100th day. Difference in the negativity of the TUNEL was imperceptible between the analyzed times, nevertheless it was evidenced that the oocytes collected on the 10th day evidenced higher maturation percentile compared to those collected on the 100th day (55.2 ± 4.9 vs 23.8 ± 4.5); c) assess the differences in milk production and composition and weight measures of F1 Holstein x Gyr primiparous cows raised in free stall barn corresponding to three groups of productive efficiency. The variables analyzed after birth such as the intake of dry feed, total milk production corrected to fat at 3,5%, milk production corrected to 305 days, daily milk production, were greater for the high efficiency cows. Cows belonging to the low efficiency group after birth showed higher weight gain and consequently higher bodily condition score when compared with cows of intermediate and high efficiency. The percentile of fat in the milk was greater for cows with low efficiency than for those of intermediate and high efficiency. The protein was equal for both high and low efficiency groups, however it was different for cows with intermediate efficiency. Lactose and ureic nitrogen in the milk were lower for cows of the low efficiency group than for those of the high efficiency group. The somatic cell count during lactation was equal for low and high efficiency cows, yet cows with intermediate efficiency showed lower count.